2015
DOI: 10.1007/s10551-015-2863-2
|View full text |Cite
|
Sign up to set email alerts
|

How Ethically Would Americans and Chinese Negotiate? The Effect of Intra-cultural Versus Inter-cultural Negotiations

Abstract: A growing body of research has started to examine how individuals from different countries may differ in their use of ethically questionable tactics during business negotiations. Whereas prior research focused on the main effect of the national culture or nationality of the negotiator, we add a new factor, which is the nationality of the counterpart. Looking at both these variables allows us to examine whether and how people may change their likelihood of using ethically questionable tactics in intercultural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The validation of previous studies' classification of questionable negotiation tactics into three groups, namely, pretending, deceiving and lying, in Austria, has the potential to generalize this classification cross-culturally. Furthermore, although current literature has been increasingly assessing the ethicality of negotiation strategies in non-Western cultural contexts (Xiao and Ma, 2015;Yang et al, 2017), ethically questionable negotiation tactics within Germanic contexts have been largely underexplored. Therefore, research outcomes regarding negotiation tactics in Austria may extend existing intra-cultural and inter-cultural research, generating valuable conclusions for both theory and practice.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of previous studies' classification of questionable negotiation tactics into three groups, namely, pretending, deceiving and lying, in Austria, has the potential to generalize this classification cross-culturally. Furthermore, although current literature has been increasingly assessing the ethicality of negotiation strategies in non-Western cultural contexts (Xiao and Ma, 2015;Yang et al, 2017), ethically questionable negotiation tactics within Germanic contexts have been largely underexplored. Therefore, research outcomes regarding negotiation tactics in Austria may extend existing intra-cultural and inter-cultural research, generating valuable conclusions for both theory and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike crowdsourcing services such as MTurk, whose participant base has been described as “professional survey‐takers” (Peer et al, 2017, p. 153), Changsha Ranxing IT delivers bespoke participant recruitment on a project‐by‐project basis. As a result, studies using this service have been proven to yield high‐quality data (Xu & Ma, 2016; Yang et al, 2017; Zhou et al, 2012). Participants' mean age was 30.51 (SD = 5.40), 66% were female, with a mean job tenure of 6.34 years (SD = 4.43), and, one average, 3.81 years (SD = 2.96) of experience in recruitment and selection, such as conducting job interviews and selecting applicants to fill vacancies.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of cognition, some researchers focused on the specific behaviors displayed by negotiators in cross-cultural negotiations [45][46][47]. It is important to consider culture in studying negotiation behaviors, because culture determines specific values that dominate the negotiators' behaviors [45].…”
Section: Cross-cultural Negotiation: Focus On Cognition and Behaviormentioning
confidence: 99%
“…Tinsley and Pillutla [46] found that American negotiators were more likely to adopt self-interest and joint problem-solving norms whereas Hong Kong Chinese tended to adopt an equality norm and behave accordingly. Americans and Chinese differed in using ethically questionable tactics in negotiations depending on the nationality of the counterpart [47].…”
Section: Cross-cultural Negotiation: Focus On Cognition and Behaviormentioning
confidence: 99%